LA MORS LITIS NEL PROCESSO CIVILE ITALIANO DAL C.P.C. DEL 1865 AL C.P.C. DEL 1940 - Fuiano, Mario Pio (Cordis: Revista Eletrônica de História Social da Cidade, 2021)
The author, through the  historical  analysis  of the extinction of the proceedings, aims to show how the crisis of civil justice in Italy is due to the idea – of fascist origin – that all trials must proceed quickly, even against the will of the parties.